PENGAWASAN POLITIK UANG PADA PEMILIHAN UMUM LEGISLATIF 2019 OLEH BAWASLU KOTA PEKANBARU - Rizki, M. Aidil; ", Hasanuddin (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2021)
This study aims to describe the supervision of money politics in the 2019 legislative general election conducted by the Pekanbaru City Bawaslu and to find out what factors influence the process of monitoring money politics in the 2019 legislative general election by the Pekanbaru City Bawaslu. The approach used in this research is a qualitative approach with a descriptive type, the place of research is the Pekanbaru City Election Supervisory Board. Data collection techniques using the method of observation, interviews, and documentation. The data analysis technique uses descriptive qualitative analysis starting from problem formulation, data collection, data reduction, data presentation to drawing conclusions. Test the validity of the data using triangulation and checking techniques.Based on the results of the study, it can be concluded that the supervision of money politics carried out by the Pekanbaru City Bawaslu in the 2019 Legislative Election in Pekanbaru City in this study, the first is in the form of Preparation Stages for Election Oversight which at this stage is divided into 5 categories, namely: Preparation for Supervision, Division of Supervisory Implementers, Locus and Focus of Supervision, Regulation/Assessment of Political Money, and the last is Controlling Time Management. In accordance with Law no. 7 of 2017 which states that Bawaslu focuses on monitoring money politics on prevention efforts, which consist of monitoring plans and monitoring activities. Of the 5 stages above, according to the researcher, the preparation stage for monitoring money politics is the most crucial in conducting supervision. After optimal preparation, the next step is to evaluate. Assessment is intended to compare plans with achievements. According to the researcher, Bawaslu's achievements in terms of monitoring money politics have not been maximizSupporting factors for the occurrence of Money Politics include: Tradition, ambition of candidates / thirst for power, supportive environment, weak law enforcement, economic factors, and low public knowledge about politics. While the factors that hinder the process of monitoring money politics by the Bawaslu include: Difficulty in proving money politics practices because the formulation and elements of punishment in the legislation are not yet rigid. People tend not to dare to report to the Bawaslu and the Gakkumdu center. Low public awareness and knowledge of the practice of money politics. The author's suggestion is to the Pekanbaru City Bawaslu and the ranks of election organizers to optimize it again in coordinating in terms of supervision so that it is carried out better. Bawaslu must also be able to make maximum efforts to eliminate the factors that are driving the occurrence of money politics. Bawaslu instills a moralistic system, namely prevention through moral punishment or social witnesses. This system will strengthen moral values so that it is expected to be able to suppress the crime of money politics in the midst of society.Keywords: Supervision, Bawaslu, Money Politics